Prenatal Care Utilization Rate and Patients Satisfaction - ST Mirmolaei; Z Khakbazan; A Kazemnejad; M Azari (Tehran University of Medical Sciences, 2007)
Background & Objective: Studies show, clients;apos satisfaction is an important indicator for service quality assessment. Finding causes of dissatisfaction helps to promote health care services quality.  High quality prenatal care services and clients;apos satisfaction decreases maternal and neonatal mortality and morbidity. The perceived quality of the prenatal care by the mothers can not be effectively evaluated unless considering the opinions, demands and satisfaction rate of mothers who receive the care. The objective of this study is to measure prenatal care utilization rate and patients satisfaction in the clinics of Tehran University of Medical Sciences in 2005.Methods & Materials: In this cross-sectional study, 380 pregnant women who had received prenatal care services in two hospitals and eight health centers were selected randomly and interviewed. Data were gathered using a questionnaire including demographic characteristics and satisfaction questions. Data were analyzed using SPSS and tested with chi-square and Pearson exact test.Results: According to the results, 53.4 % and 14.8% of the pregnant women had received complete and incomplete prenatal care, respectively. Most of the pregnant women (54.7%) were completely satisfied, 23.7% and 21.6% were moderately and poorly satisfied, respectively. There was a significant relationship between the utilization rate and satisfaction of mothers (P<0.001). 53.4% of mothers in health centers and 46% in hospitals had received complete prenatal care. Satisfaction with prenatal care in health centers and hospitals were 57.5% and 47%, respectively. This difference was probably related to the amount of emotional and physical care received by the patients in the different settings and the characteristics of the centers in which these services are provided. The kind of setting had significant relationship with the utilization and satisfaction rates (P=0.003, P=0.005, respectively). The results showed that the utilization and satisfaction rates in the health centers in which health-care providers were midwives were better than the hospitals in which health-care providers were medical and midwifery students. But in both settings it was lower than 60%.Conclusion: As a result, the utilization rate and satisfaction of mothers were inadequate in health centers and hospitals (lower than 70%). In the hospitals, they were lower than the health centers. The standardization of prenatal care and improvement of educational programs in hospitals should be considered.